Sperm DNA fragmentation : implications in assisted reproductive technologies - Hoogendijk, Christiaan F. (Christiaan Frederik) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2007.